LncRNA TCONS_00145741 Knockdown Prevents Thrombin-Induced M1 Differentiation of Microglia in Intracerebral Hemorrhage by Enhancing the Interaction Between DUSP6 and JNK - Wu, Lanxiang; Zhan, Qingqing; Liu, Pan; Zheng, Heqing; Liu, Mingxu; Min, Jun; Xie, Liang; Wu, Wei (Frontiers in Cell and Developmental Biology, 2022)
Background: The differentiation of microglia from M1 to M2 exerts a pivotal role in the aggression of intracerebral hemorrhage (ICH), and long non-coding RNAs (lncRNAs) are associated with the differentiation of microglia. However, the underlying mechanism had not been fully clarified. Methods: The expression profile of lncRNAs in thrombin-induced primary microglia was analyzed by RNA sequencing. Under thrombin treatment, the effect of lncRNA TCONS_00145741 on the differentiation of microglia was determined by immunofluorescence staining, quantitative real-time PCR, and Western blot. The potential mechanism and related signaling pathways of TCONS_00145741 in the M1 and M2 differentiation of microglia in ICH were assessed by Gene Ontology analysis, flow cytometry, RNA pull-down, RNA Immunoprecipitation, and RNA fluorescence in situ hybridization followed by immunofluorescence analysis. Results: LncRNA TCONS_00145741 expression was elevated in the thrombin-induced primary microglia, and the interference with TCONS_00145741 restrained the M1 differentiation of microglia and facilitated the M2 differentiation under thrombin treatment. The interference with TCONS_00145741 restrained the activation of the JNK pathway in microglia under thrombin treatment and repressed the JNK phosphorylation levels by enhancing the interaction between DUSP6 and JNK. In vivo experiments further illustrated that the interference with TCONS_00145741 alleviated ICH. Conclusion: LncRNA TCONS_00145741 knockdown prevented thrombin-induced M1 differentiation of microglia in ICH by enhancing the interaction between DUSP6 and JNK. This study might provide a promising target for the clinical treatment of ICH.